The Political Economy of Restructuring and Subsidisation: An International Perspective - Greetje Everaert (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
In today's increasingly competitive business environment, many firms in declining industries have been confronted with the need to restructure. However, lobbies in these industries have often managed to attract government subsidies instead. The current paper looks at the decision of loss-making firms whether to lobby for subsidies or whether to restructure in the context of a contributions game as in Magee et al. (1989). We also analyse the role of tariffs in restricting uncompetitive practices such as granting state aid to unprofitable firms. Several results stand out. Firstly, there is a trade-off between spending resources on lobbying for subsidies and costly restructuring such that both restructuring and subsidisation take place in our model. Secondly, countervailing tariffs on subsidised exports shift the decision in favour of restructuring, thereby hardening budget constraints. Thus, the model shows that external constraints such as countervailing tariffs can help to establish internal financial discipline. Thirdly, a social planner always prefers full restructuring implying that political competition comes at a cost of lower economic welfare in our model.
Keywords: P26; F13; 330; Soft Budget Constraints; Restructuring; Political Economy; Lobbying; Trade Policy; Declining Industries; Organisatorischer Wandel; Budgetrestriktion; Industriesubvention; Interessenpolitik; Schrumpfungsbranche; Internationaler Wettbewerb; Theorie